From Rhetoric to Aesthetics. - Bicanová, Klára (Masarykova univerzita, 2013)
The thesis deals primarily with the term wit and its modern and historical usage in literary and aesthetic theories. Further, it concerned with the literary and aesthetic implications of the terms wit and esprit as they were theorized in critical writings of several authors of the early modern England and France. The thesis has two primary goals. The first goal is to re-assess the English concept of wit, nowadays regarded as an out-dated device of past poetic systems, and to present it as vital and useful part of the contemporary discourse. The second goal is to provide comparative reading of.